Building transformative capacity in southern Africa: Surfacing knowledge and challenging structures through participatory Vulnerability and Risk Assessments. Issue 1 (March 2019) - Morchain, Daniel; Spear, Dian; Ziervogel, Gina; Masundire, Hillary; Angula, Margaret N; Davies, Julia; Molefe, Chandapiwa; Hegga, Salma
Although participatory approaches are becoming more widespread, to date vulnerability assessments have largely been conducted by technocrats and have paid little attention to underlying causes of vulnerability, such as inequality and biased governance systems. Participatory assessments that recognise the social roots of vulnerability, however, are critical in helping individuals and institutions rethink their understanding of and responses to climate change impacts. This paper interrogates the contribution of Oxfam's Vulnerability and Risk Assessment methodology to enabling transformation at both personal and institutional levels. Three Vulnerability and Risk Assessment exercises were conducted in Malawi, Botswana and Namibia by one or more of the authors in 2015 and 2016. Reflecting on these workshops, we explore the contribution that a process like the Vulnerability and Risk Assessment may bring to transformation. We conclude that these types of inclusive and representative participatory approaches can shift narratives and power dynamics, allow marginal voices to be heard, build cross–scalar relationships and enable the co-creation of solutions. Such approaches can play a key role in moving towards transformational thinking and action, especially in relation to climate change adaptation.